In2Se3 saturable absorber for generating tunable Q-switched outputs from a bismuth–erbium doped fiber laser. (27th September 2018) - Ahmad, H; Zulkifli, A Z; Yasin, M; Ismail, M F; Thambiratnam, K
Abstract: An Indium–selenide based saturable absorber is proposed and demonstrated for the passive generation of Q-switched pulses in a C- to L-band fiber laser. The proposed laser uses a 21 cm long bismuth–erbium doped fiber (Bi-EDF) as the linear gain medium, and is capable of generating passively Q-switched outputs that can be tuned over a bandwidth of 40 nm from 1533 nm to 1573 nm. The generated pulses have a maximum repetition rate of 52 kHz and a minimum pulse width of 2.2 μ s at the maximum available pump power of 134 mW. Similarly, a maximum pulse energy and average output power of 13.5 nJ and 0.7 mW respectively are obtained at the same pump power. Radio frequency measurement indicates a stable pulse obtained with a high signal-to-noise ratio of 42.8 dB and with no other frequency peaks observed, indicating that only the fundamental mode is present. The proposed tunable Q-switched Bi-EDF laser would have significant potential for applications requiring tunable, high energy pulses such as spectroscopy and medicine in the C- and L-band regions.